2014
DOI: 10.1016/j.memsci.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Low-biofouling membranes prepared by liquid-induced phase separation of the PVDF/polystyrene-b-poly (ethylene glycol) methacrylate blend

Abstract: In the present work, the focus is laid on the formation, and low-biofouling properties of polyvinylidene fluoride (PVDF) membranes modified using an amphiphilic copolymer additive: polystyrene-b-poly (ethylene glycol) methacrylate (PS-b-PEGMA). PVDF was blended with PS-b-PEGMA and membranes were prepared by liquid-induced phase separation. The additive played a significant role on membrane formation, slightly decreasing surface porosity, reducing the shrinkage during phase separation, and increasing both the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(54 citation statements)
references
References 51 publications
4
50
0
Order By: Relevance
“…Among these materials, PEO-like polymers have attracted much attention due to their superior antifouling ability [37]. Although the kinetic and thermodynamic reasons for the protein resistance of PEO are still controversial, many researchers have attempted to mix the various PEO-containing amphiphilic copolymers with the usually used membrane materials to prepare the antifouling membranes [10][11][12][13][14][15][16][17][18][19][20][21]. The results confirmed that PEO chain had a trend to enrich on the membrane surface, which imparted good hydrophilicity to the hydrophobic membranes.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Among these materials, PEO-like polymers have attracted much attention due to their superior antifouling ability [37]. Although the kinetic and thermodynamic reasons for the protein resistance of PEO are still controversial, many researchers have attempted to mix the various PEO-containing amphiphilic copolymers with the usually used membrane materials to prepare the antifouling membranes [10][11][12][13][14][15][16][17][18][19][20][21]. The results confirmed that PEO chain had a trend to enrich on the membrane surface, which imparted good hydrophilicity to the hydrophobic membranes.…”
Section: Introductionmentioning
confidence: 89%
“…It is generally accepted that improving the intrinsic hydrophobic character of membranes is the most common method to avoid the non-specific adsorption between membrane and solute. Several hydrophilic materials were used to enhance antifouling ability of the conventional hydrophobic membranes, including PEO-like polymers [10][11][12][13][14][15][16][17][18][19][20][21][22], zwitterionic polymer [23][24][25], phospholipid polymer [26,27], heparin [28,29], zirconium oxide [30], titanium oxide [31], zeolite [32], silica [33], carbon nanotubes [34], graphene oxide [35], and their mixture [36]. Among these materials, PEO-like polymers have attracted much attention due to their superior antifouling ability [37].…”
Section: Introductionmentioning
confidence: 99%
“…Oppositely, immersing the polymer system would have directly led to the formation of a finger-like structure with a dense and smooth skin (WCA of about 85 ° [35] ). Therefore, the role of methanol is critical.…”
Section: Pvdf Membranes Formed By Lips Process and Surface-modified mentioning
confidence: 99%
“…It also presented a tensile strength at break in the same range as that reported by Peng et al . ( < 1 MPa) [35] , which is rather low, but still enabled them to apply the membranes in membrane distillation. Therefore, it was believed that mechanical properties of the as-prepared membrane would be good enough to sustain a gravity-driven filtration process without being damaged.…”
Section: Structure Related Propertiesmentioning
confidence: 99%
“…Many studies showed that compared to uncoated membranes, less fouling was observed when membranes surfaces had a hydrophilic coating [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%